Growth of crossbred Jersey x Holstein heifers compared to Holstein - Rodrigues, Rafael Sachet (2014)
Milk production in subtropical regions is mostly based in straigthbreds thoroughbred cows. Recently, the practice of crossbreeding between dairy breeds has become more popular in southern Brazil and has motivated this paper. The objective of this work was to compare growth of crossbred Holstein x Jersey in relation to the Holstein thoroughbred heifers. Evaluations have been carried out using data of three dairy herds in the states of Santa Catarina and Paraná, which have in their breeding stock Holstein and Holstein x Jersey crossbred cows. The growth indicators used were height at withers and body weight, estimated from chest girth. We analyzed 427 measurements of 133 heifers from two to 24 months of age, from February 2008 to January 2009. The females were grouped into three genetic groups (Holstein, ¾ and ⅝ Holstein, ½ Holstein x Jersey - F1) and data submitted for analysis of variance. Holstein heifers exceeded crossbreds in body weight and height at withers, however, there was no difference between F1 crossbred animals and a higher proportion of Holstein (¾ and ⅝). The means ± standard errors for body weight were 278.1±2.95, 253.1±2.63 and 250.1±4.36 and for height at withers were 119.1±0.40, 113.1±0.36 and 111.9±0.60, respectively, for Holstein, ¾ and ⅝ Holstein and F1. There was an interaction between the effects of genetic groups and age of animals on the weight and height. From the regression equations of the effect of age on body weight estimated for all genetic groups, we can estimate for F1 crossbreds weghts equivalent to 84 and 89% of the Holstein thoroughbreds at 15 and 24 months of age, respectively, and for ¾ and ⅝ Holstein these weights were equivalent to 91 and 87%, respectively. We are concluded that Holstein x Jersey crossbred heifers show lower growth than the thoroughbred Holstein. They should be handled differently, especially regarding the weight at insemination.